Blood lactate and oxygen consumption in soccer players: comparison between different positions on the field - Santos-Silva,Paulo Roberto (2017)
OBJECTIVE: We hypothesize that in players with better aerobic fitness, lactate production was not inhibited after high-intensity exercise, regardless of the footballer's position on the field. METHOD: Sixty professional male soccer players performed cardiopulmonary exercise tests on an ergometric treadmill; respiratory gas exchanges were monitored throughout and blood lactate levels at peak effort was measured, using a portable device. The heart rate response was determined by computerized EKG. Training sessions took place over an average of ten hours per week, and the players had 6.8 years of experience in competitive soccer; they were tested a third of way into the season. The positions tested were (centerback, fullback, midfielder and striker). RESULTS: The following results (mean ± std. dev.) were obtained: (1) peak oxygen consumption of 58.8 ± 4.5 ml.kg-1.min.-1; (2), blood peak lactate of 12.3 ± 1.6 mmol.L-1; (3) maximum heart rate of 193 ± 3.3 beats. min-1; (4); oxygen consumption at the second ventilatory threshold of 49.6 ± 5.0 mL. kg-1.min-1; (5); running speed at the second ventilatory threshold of 13.3 ± 0.8 km.h-1; (6) percentage of oxygen consumption in the second ventilatory threshold of 84 ± 6%. There was no correlation between maximum aerobic level vs. peak lactate concentration (r = -0,031; p = 0.812), nor between submaximal aerobic level vs. peak lactate concentration (r = -0.146; p = 0.335) in the positions tested. CONCLUSION: Better or worse aerobic profiles according to game positions in soccer players do not influence peak lactate levels following high-intensity exercise, and confirms the study hypothesis.